Stabilization of Soft Clay Using Waste-Based Cement - Nontananandh, Supakij; Yoobanpot , Naphol (Agriculture and Natural Resources, 2012)
This research focused on the potential utilization of waste-based cement (WBC) as a stabilizer to improve the compressive strength of soft clay and also aimed to verify the hardening effects of WBC compared to ordinary Portland cement (OPC). Evaluation of hardening effects was performed based on the compressive strength test and by means of physicochemical tests. The experimental results revealed that the unconﬁ ned compressive strengths of soil mixes can be improved by stabilizing with WBC to a similar extent to that achieved using OPC. The improvement in strength was due to the enhancement of hydration producing calcium silicate hydrate and calcium aluminate hydrate.